(untitled) (Physical Education, Health and Social Sciences, 2025)
Plastic pollution poses a significant environmental threat, with polyethylene (PE) being one of the most persistent polymers. Conventional recycling methods have limitations, necessitating innovative degradation approaches. In this study, Se⁴⁺-doped TiO₂ (TSe) nanocatalysts were synthesized via the sol-gel method with varying selenium concentrations (0.1–1 w/w%) to enhance photocatalytic performance under visible light. Characterization using XRD, Raman, BET, SEM, FTIR, PL, and UV/Vis spectroscopy confirmed successful doping, structural modifications, and a reduced bandgap (minimum 2.7 eV). Photocatalytic degradation of PE was evaluated, revealing that TSe0.5 exhibited optimal performance with a degradation efficiency of 92.2% and a recyclability of 10 cycles at 52.76% efficiency. Response surface methodology (RSM) was applied to optimize pH, temperature, and catalyst concentration, demonstrating a significant impact on degradation efficiency. The enhanced photocatalytic activity was attributed to Se⁴⁺ incorporation, leading to improved charge carrier separation, increased surface area, and extended visible light absorption. These findings highlight the potential of Se-doped TiO₂ nanocatalysts for efficient and sustainable PE degradation